Multifunctional Metasurface Lens With Tunable Focus Based on Phase Transition Material - Song, Yongkang; Liu, Weici; Wang, Xiaolei; Wang, Faqiang; Wei, Zhongchao; Meng, Hongyun; Lin, Ning; Zhang, Hongqiang (Frontiers in Physics, 2021)
Metasurfaces have powerful light field manipulation capabilities, which have been extensively studied in the past few years and have developed rapidly in various fields. At present, the focus of metasurface research has shifted to the tunable field. In this paper, a temperature-controllable multifunctional metasurface lens based on phase transition material is designed. First of all, by controlling the temperature of the desired working area and the polarization of the incident light, switching among multiple focus, single focus and no focus at any position can be achieved, and the intensity and helicity of the output light can be adjusted. In addition, a polarization-insensitive intensity tunable metalens based on the P-B phase principle is designed, when the incident light is linearly polarized light, left-handed circularly polarized light, or right-handed circularly polarized light, it has the same focal point but with different light field intensities. Therefore, the focus intensity is dependent on the helicity of the incident light.